The MIEL1‐ABI5/MYB30 regulatory module fine tunes abscisic acid signaling during seed germination. Issue 4 (5th April 2022) - Nie, Kaili; Zhao, Hongyun; Wang, Xiaopei; Niu, Yanli; Zhou, Huapeng; Zheng, Yuan
Abstract: The transcription factor ABSCISIC ACID INSENSITIVE5 (ABI5) plays a crucial role in abscisic acid (ABA) signaling during seed germination. However, how ABI5 is regulated during this process is poorly understood. Here, we report that the ubiquitin E3 ligase MIEL1 and its target transcription factor MYB30 modulate ABA responses in Arabidopsis thaliana during seed germination and seedling establishment via the precise regulation of ABI5. MIEL1 interacts with and ubiquitinates ABI5 to facilitate its degradation during germination. The transcription factor MYB30, whose turnover is mediated by MIEL1 during seed germination, also interacts with ABI5 to interfere with its transcriptional activity. MYB30 functions downstream of MIEL1 in the ABA response, and both are epistatic to ABI5 in ABA‐mediated inhibition of seed germination and postgerminative growth. ABA treatment induces the degradation of MIEL1 and represses the interaction between MIEL1 and ABI5/MYB30, thus releasing both ABI5 and MYB30. Our results demonstrate that MIEL1 directly mediates the proteasomal degradation of ABI5 and inhibits its activity via the release of its target protein MYB30, thus ensuring precise ABA signaling during seed germination and seedling establishment. Abstract : Releasing the restriction imposed by abscisic acid (ABA) allows seed germination. ABA‐INSENSITIVE5 (ABI5) is the major ABA activator during germination and the MYB30‐INTERACTING E3 LIGASE1‐ABI5‐MYB30 regulatory module fine tunes ABA signaling during germination via precising regulation of ABI5.